Icariin stimulates differentiation of bone marrow-derived mesenchymal stem cells (BM-MSCs) through activation of cAMP/PKA/CREB - Dan Lou; Jifeng Ye; Lianhua Yang; Zheng Wu; Wei Zheng; Hui Zhang (Universidade de São Paulo, 2019)
Icariin, a prenylated flavonol glycoside isolated from Epimedium, has been considered as a potential alternative therapy for osteoporosis. The present study aimed to clarify the detailed molecular mechanisms of action of icariin on osteoblast function, using bone marrow-derived mesenchymal stem cells (BM-MSCs). BM-MSCs were first stimulated by icariin. Then, gene and protein expression of cAMP/PKA/CREB signaling molecules were analyzed by RT-PCR and western blotting (WB), and alkaline phosphatase (ALP) was analyzed in cell lysates by ELISA. MTT assays indicated that icariin did not have significant effects on cell viability up to 1 µM. Icariin showed a dose-dependent effect on the alkaline phosphatase activity of BM-MSCs. WB analysis showed that icariin treatment of BM-MSCs significantly enhanced the protein expression of protein kinase A (PKA) and cAMP-responsive element binding protein (CREB), while RT-PCR results showed that icariin dose-dependently increased the mRNA levels of PKA and CREB. Icariin induced BM-MSC differentiation by BMP2, Smad1, and Runx2. RT-PCR and WB results indicated that icariin significantly increased the expression of BMP2, Smad1, and Runx2 in BM-MSCs. These results suggest that icariin is an agonist of the cAMP/PKA/CREB pathway in BM-MSC differentiation, raising the possibility that it could be used in the treatment of osteoporosis.